A companhia de navegação fluvial de Jacob Arnt no Vale do Taquari – RS - Teresinha Maria Furlanetto Marques (Navigator)
The navigation by the Taquari river was a development factor for its basin and the state of Rio Grande do Sul. German immigrants created navigation companies as soon as they arrived at the XIXth century, because they needed rapid means of transport to attend their needs. The company of navigation Arnt, carrying things and people, was the most important riverboat company in this state. This activity was no doubt an important development factor for the State of Rio Grande do Sul.